Principles Of Teaching Russian Language - Abduraxmanova Dilbarxon Abdullaxamidovna (Zien Journals, 2024)
The proposed material will help students to properly organize their activities not only in preparation for practical classes and exams in the subject, but also during teaching practice in the Russian language. The article is addressed to philology students, teachers of Russian language methods, practicing teachers , as well as literature teachers. The proposed material will be useful and interesting to everyone who seeks to diversify the forms of mastering the course of methods of teaching the Russian language, work on the subject. The material is addressed to the possibilities of developing students' analytical thinking, to the prospects for solving innovative problems of modern teaching of the Russian language. In addition, classifications of teaching principles and methods are proposed that allow the teacher to see the design of the educational process in perspective; those used in modern educational institutions are analyzed
Keywords: principles; functions of language; unit of language; typology